2017
DOI: 10.1007/s00360-017-1061-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in oxidative stress resistance in relation to longevity in Drosophila melanogaster

Abstract: Gender differences in lifespan and aging are known across species. Sex differences in longevity within a species can be useful to understand sex-specific aging. Drosophila melanogaster is a good model to study the problem of sex differences in longevity since females are longer lived than males. There is evidence that stress resistance influences longevity. The objective of this study was to investigate if there is a relationship between sex differences in longevity and oxidative stress resistance in D. melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 67 publications
4
38
1
Order By: Relevance
“…Independent of food type and age, females were more resistant to hydrogen peroxide than males with a high percentage of females (about Diet: p = 0.7413 Age: p < 0.0001 Gender: p = 0.4690 Diet×age: p = 0.9615 Diet×gender: p = 0.7415 Age×gender: p = 0.9836 Diet×age×gender: p = 0.9846 A 60-80%) still alive after 48 h whereas less than 10% of males were alive. Similar sex-specific differences in oxidative stress resistance in relation to longevity have been reported recently [16]. Previously, we did not find any effects of dietary AKG on oxidative stress resistance in 24-day old w 1118 females and the same was true here.…”
Section: Resultssupporting
confidence: 93%
“…Independent of food type and age, females were more resistant to hydrogen peroxide than males with a high percentage of females (about Diet: p = 0.7413 Age: p < 0.0001 Gender: p = 0.4690 Diet×age: p = 0.9615 Diet×gender: p = 0.7415 Age×gender: p = 0.9836 Diet×age×gender: p = 0.9846 A 60-80%) still alive after 48 h whereas less than 10% of males were alive. Similar sex-specific differences in oxidative stress resistance in relation to longevity have been reported recently [16]. Previously, we did not find any effects of dietary AKG on oxidative stress resistance in 24-day old w 1118 females and the same was true here.…”
Section: Resultssupporting
confidence: 93%
“…Locomotion determination was done using the negative geotaxis experiment as described by Niveditha [ 14 ] at the end of the MSG feed exposure period. A transparent plastic ring tube which would hold 10 flies at once of standard length, 25 cm was secured on a tripod stand.…”
Section: Main Textmentioning
confidence: 99%
“…Bearing in mind that D. melanogaster have an established toxicological advantage due to their large population numbers and short lifecycle [ 12 , 13 ], there was a need to examine MSG exposure in D. melanogaster over a longer period. In addition, oxidative stress in D. melanogaster has been found to decrease with an increase in age [ 14 ], showing the role of the experimental period in toxicological evaluation of MSG. The objective of the study was to determine effects of MSG supplementation on hydrogen peroxide scavenging activity, catalase activity, negative geotaxis, and lifespan in male D. melanogaster .…”
Section: Introductionmentioning
confidence: 99%
“…The effects of oxidative stress have been proven to differ substantially between sexes. Under exposure to ethanol, Drosophila melanogaster females exhibited higher resistance to oxidative stress as evident from lower mortality and ROS levels as well as higher activities of antioxidant enzymes [ 12 ]. Similarly, studies in rats have found higher protection from antioxidant enzymes and lower oxidative damage in females [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%